Akuntansi Syariah Sebagai Sistem Informasi - Junita Putri Rajana Harahap; Murni Dahlena Nasution; Reza Hanafi Lubis (Forum Kerjasama Pendidikan Tinggi, 2023)
As an information system, accounting refers to gathering and disseminating economic data about a company entity to numerous parties. The management of our economic and social system depends heavily on accounting, which is at the forefront of this field. Decisions made by people, governments, and other economic entities are based on how they utilise the resources that belong to a country. The financial component and financial reporting records of an entity are among the most crucial elements since they have a significant influence on the company's viability. There is no outside research involved in this study. Finding out how Islamic accounting functions as an information system is the aim of this study. The content analysis method is the analytical technique applied. Based on the study's findings, Islamic accounting is an attempt to transform modern accounting into a humanist and moral system. Islamic accounting information systems emphasize Islamic values in both the accounting process and the underlying information systems. These systems have a heavy moral burden.